Study Habits: Probing Modern Attempts to Assess Minority Offender Disproportionality - Davies, Sharon L. (2003)
Oregon, Washington and Utah have recently taken empirical steps to assess the extent to which minorities are overrepresented in their respective criminal justice systems and to seek out the root causes of any overrepresentation observed. Davies contrasts and critiques the disparate analytical approaches utilized by these states and offers some thoughts about how people might improve the chances of success of future similar efforts